CmRCC1 Gene From Pumpkin Confers Cold Tolerance in Tobacco by Modulating Root Architecture and Photosynthetic Activity - Wang, Mengmeng; Zhou, Shu; Lu, Junyang; Xu, Anqi; Huang, Yuan; Bie, Zhilong; Cheng, Fei (Frontiers in Plant Science, 2021)
Low-temperature stress is the main limiting factor of cucurbit crop cultivation as it affects crop yield and quality. The identification of genes involved in cold tolerance is a crucial aspect of pumpkin rootstock breeding. Here, we examined the function of a pumpkin Regulator of Chromosome Condensation 1 (CmRCC1) gene in the root development and cold stress responses of tobacco (Nicotiana benthamiana). CmRCC1 expression was differentially induced in pumpkin root, stem, and leaf under cold stress. Transient transformation showed that CmRCC1 is located in the nucleus. CmRCC1 overexpression in tobacco increased the gravitropic set-point angle in lateral roots, as well as root diameter and volume. The expression of auxin polar transport factors, PIN1 and PIN3, respectively decreased and increased in CmRCC1-overexpressed plants. Yeast two-hybrid verification and luciferase complementation imaging assay showed that CmRCC1 interacts with CmLAZY1. Furthermore, the decreases in maximum quantum yield of PS II, the effective quantum yield of PS II, and electron transfer rate and the increases in quantum yield of nonregulated energy dissipation and malondialdehyde content were compromised in transgenic plants compared with wild-type plants under cold stress. The results suggest that CmRCC1 plays an important role in the regulation of root architecture and positively modulates cold tolerance.